1987
DOI: 10.1111/j.1365-2125.1987.tb03143.x
|View full text |Cite
|
Sign up to set email alerts
|

Does regular treatment with ketotifen inhibit bronchoconstriction induced by isocapnic hyperventilation?

Abstract: Eight asthmatic patients completed a 12-week, double-blind, placebo controlled study to assess the efficacy of ketotifen, 1 mg twice daily, in the inhibition of bronchoconstriction induced by isocapnic hyperventilation (IH). There was no significant difference in the degree of bronchoconstriction produced by IH after treatment with ketotifen or placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
1990
1990

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It may be argued that the duration of treatment and dose used in the present study were not appropriate. Indeed, although it has been suggested that the maximum effect of ketotifen may not be achieved until 5 weeks after treatment [24], in a recent study ketotifen did not inhibit bronchoconstriction induced by eucapnic hyperventilation in subjects treated for 6 weeks [25]. We planned a 1 -week treatment because we assumed that compliance of subjects is better with shorter periods, and also because in previous studies a 1-week treatment with inhaled steroids was sufficient to provide protection [ 14,15].…”
Section: Discussionmentioning
confidence: 99%
“…It may be argued that the duration of treatment and dose used in the present study were not appropriate. Indeed, although it has been suggested that the maximum effect of ketotifen may not be achieved until 5 weeks after treatment [24], in a recent study ketotifen did not inhibit bronchoconstriction induced by eucapnic hyperventilation in subjects treated for 6 weeks [25]. We planned a 1 -week treatment because we assumed that compliance of subjects is better with shorter periods, and also because in previous studies a 1-week treatment with inhaled steroids was sufficient to provide protection [ 14,15].…”
Section: Discussionmentioning
confidence: 99%
“…water, cold air and AMP challenges but not methacholine-and LTC4-induced bronchoconstriction [68.77-80], while ketotifen is reported not to be effective against acetylcholine. isocapnic hyperventilation and sulphur dioxide challenges but may be useful for aspirin-and benzoic acid-induced asthma [63,[81][82][83]. This suggests that some types ofasthma may be more amenable than others to H iantihistamine blockade and that activity against a particular challenge may be related to a specific drug.…”
Section: Mechanisms Of Action Pertinent To the Treatment Of Allergic mentioning
confidence: 99%